Single Dose of Dietary Supplement Nutrex Lipo-6 Black® Limits the Post Exercise Hypotension Induced by Aerobic Exercise in Young Adults - Magalhães, Leonardo Medeiros; de Oliveira, Caio Victor Coutinho; Gonçalves, Maria da Conceição Rodrigues; de Souza , Alesandra Araújo; Silva, Alexandre Sérgio (Journal of Pharmacy and Nutrition Sciences, 2013)
Objective: to evaluate the blood pressure (BP) behavior and sympathetic activity in response to an aerobic exercise session after taking a dose of Nutrex Lipo-6 Black®. Methods: This randomized, placebo-controlled study utilized seventeen subjects, divided in supplementation (n=10, 26.5±5.3 years) and placebo groups (n=7, 22.4±2.8 years). They ingested a dose of Nutrex Lipo-6 Black® (containing synephrine, caffeine, yohimbine and diiodine) or placebo and underwent a session of 40min of aerobic exercise of moderate intensity. Heart rate (HR), BP and cardiac autonomic balance (measured by heart rate variability) (CANA) were monitored at baseline, 30min after supplementation, at the end of the exercise and every 10min during a recovery period of 30min. Results: After 30min of intake, Nutrex Lipo-6 Black® and placebo groups exhibited HR, BP and CANA similar to each other and in relation to the pre-supplementation moment. At the end of the exercise all variables showed a rise in relation to rest, but without statistical difference between groups (p>0,05). Moreover, at 30min of recovery, the Nutrex Lipo-6 Black® group presented with diastolic hypertensive response (increase of 4.2 mmHg) and a discrete post-exercise hypotension only to systolic pressure (-0.2 mmHg) relative to the pre-supplementation, while the placebo group showed evident both systolic and diastolic hypotension (-6.3 and -0.5 mmHg, respectively). HR and CANA were similar to pre-supplementation at this time. Conclusion: single dose of Nutrex Lipo-6 Black® is able to limit the benefits of an exercise session in reducing BP, even without affecting the resting conditions of BP and CANA.